Type D Personality Is Associated with Glycemic Control and Socio-Psychological Factors on Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study - Lin YH (Psychology Research and Behavior Management, 2020)
Yi-Hsin Lin,1 Di-An Chen,2 Chemin Lin,3 Hsuan Huang4 1Division of Endocrinology and Metabolism, Department of Internal Medicine, Taiwan Adventist Hospital, Taipei, Taiwan (R.O.C.); 2Department of Clinic Psychology, Fu Jen Catholic University, Taipei, Taiwan (R.O.C.); 3Department of Psychiatry, Keelung Chang Gung Memorial Hospital, Keelung, Taiwan (R.O.C.); 4Division of Pediatric Surgery, Department of Surgery, Mackay Memorial Hospital, Taipei, Taiwan (R.O.C.)Correspondence: Hsuan HuangDepartment of Surgery, Mackay Memorial Hospital, Taipei, Taiwan (R.O.C.)Tel +886-2-2562-7200Email smilefortw@hotmail.comPurpose: Type D personality (TDP) has been recognized as a risk factor for many diseases. The aims of our study were to estimate the prevalence of TDP and glycemic control on the patients with type 2 diabetes mellitus (T2DM) and to assess their relationship between TDP and socio-psychological factors, such as perceived stress, self-efficacy, self-care behaviors, and psychological distress.Patients and Methods: A total of 198 T2DM patients (male 62.6%, mean age 51.2± 11.0, mean HbA1c 7.3± 1.8%) were recruited consecutively from the Department of Endocrinology of a regional hospital in Taipei, Taiwan, from December 2017 to April 2018. They completed questionnaires that contain questions about sociodemographic characteristics, TDP, illness-related stress, self-efficacy, execution of diabetes management and emotional distress. Their medical records were reviewed for biomedical data.Results: Of the 198 patients, 82 (41.4%) had TDP. Controlling for sociodemographic factors, patients with TDP were reported significantly poorer on glycemic control than those without TDP (mean HbA1c (%) 7.6± 1.9 vs 7.1± 1.8, P< 0.05). Compared to those without TDP, the results showed significantly higher levels of perceived stress (P< 0.001) and psychological distress (anxiety and depression) (P< 0.001), as well as significantly lower levels of self-efficacy (P< 0.001) and self-care behaviors (P< 0.001) on patients with TDP. TDP was positively correlated with perceived stress and psychological distress and negatively correlated with self-efficacy and self-care behaviors scores.Discussion: This study provides the evidence linking TDP with poor glycemic control, low levels of self-efficacy and self-care behaviors, as well as high levels of perceived stress and psychological distress, which highlights the screening of TDP and the tailored needs for the care among T2DM patients with TDP.Keywords: Type D personality, type 2 diabetes mellitus, perceived stress, self-efficacy, self-care behaviors, psychological distress